Faktor-Faktor Resiko Terjadinya Stroke Pada Pasien Hipertensi Di Puskesmas Glugur Kota Medan - Nurul Rahmah Siregar; Helmiwati Helmiwati (Journal of Pharmaceutical and Sciences, 2023)
Stroke is one of the major problems faced throughout the world, both in developed and developing countries. An acute attack of stroke causes physical and mental disability as well as a sudden high death rate, both in productive and old age. Hypertension is a condition where a person experiences an increase in blood pressure above normal (> 140/90 mmHg) which results in mortality and mortality. This study aims to determine the risk factors for stroke in hypertensive patients at the Glugur Health Center, Medan. The case population of the study was 150 stroke sufferers, the researchers took a sample of 20%, the results of the study showed that there were 13 (43%) healthy respondents and 17 (56%) unhealthy respondents. Thus it is expected to further improve health education to patients about the benefits of a regular lifestyle or diet and exercise as needed, because an unhealthy lifestyle can cause various diseases.